Loan Loss Provisioning Behavior in Chinese Commercial Banks - YANG, JINHAN (2017)
The purposes of this paper is to investigate the determinants of loan loss provisioning within Chinese commercial banks during the time period of 2010 to 2015. This study is on the basis of relevant empirical literatures and using a panel of 62 commercial banks in China. Two model are used in the research, which is Stochastic Frontier Approach SFA) and Generalized Method of Moments (GMM), respectively. Cost-efficiency is calculated in the first stage and then being treated as one of the explanatory variables in GMM model. The GMM model is adopted to test for four loan loss provision hypotheses in Chinese banking. They are income smoothing, business cycle, capital management and either bad management or cost skimping. The results in this research provide evidence on income smoothing and cost skimping practice. More interestingly, both procyclicality and countercyclicality of loan loss provisioning behavior is verified in Chinese banking, with the former one slightly significant than the latter one. However, this study fails to find support on capital management in China.